The proprotein convertase furin in tumour progression. Issue 4 (15th May 2017) - Jaaks, Patricia; Bernasconi, Michele
Abstract : Proprotein convertases are proteases that have been implicated in the activation of a wide variety of proteins. These proteins are generally synthesised as precursor proteins and require limited proteolysis for conversion into their mature bioactive counterparts. Many of these proteins, including metalloproteases, growth factors and their receptors or adhesion molecules, have been shown to facilitate tumour formation and progression. Hence, this review will focus on the proprotein convertase furin and its role in cancer. The expression of furin has been confirmed in a large spectrum of cancers such as head and neck squamous cell carcinoma, breast cancer and rhabdomyosarcoma. Functional studies modulating furin activity uncovered its importance for the processing of many cancer‐related substrates and strongly indicate that high furin activity promotes the malignant phenotype of cancer cells. In this review, we summarise the expression and function of furin in different cancer types, discuss its role in processing cancer‐related proproteins and give examples of potential therapeutic approaches that take advantage of the proteolytic activity of furin in cancer cells.